Chronic Epidural Hematoma: Still a Rare Entity? - Banga, Manpreet Singh; Sandeep, B. V.; Dixit, Sourabh (Indian Journal of Neurotrauma, 2021)
Introduction Extradural hematoma diagnosed more than 14 days after head injury is classified as a chronic extradural hematoma (CEDH). In the present study, we presented a series of 8 patients with CEDH in a span of 6 months.Materials and Methods In this article, we reported 8 cases of CEDH who presented to Nil Ratan Sircar Medical College, Kolkata, West Bengal, India, within a span of 6 months.Discussion Extratemporal epidural hematomas (EDHs) are often due to venous bleeding from the diploic veins or dural sinuses or to delayed rupture of a middle meningeal pseudoaneurysm. In these cases, cerebrospinal fluid may redistribute from the lateral ventricles and thus allowing room for the enlarging hematoma producing vague neurological symptoms and signs. The incidence rate of CEDH reported in the literature ranges from 3.9 to 30% of all EDHs. Computed tomography (CT) scan in CEDH often shows a low-density center surrounded by a high-density margin. Calcification of the displaced dura mater may also occur. Some are identified incidentally, whereas others are diagnosed when investigating for persistent and/or progressive neurological symptoms. Symptomatic CEDH should be surgically evacuated and has an excellent outcome the earlier it is done. In patients with no or mild symptoms, normal neurological status, and a small-sized CEDH spontaneous resolution may be expected.Conclusion In the post-CT era, it is always said that CEDH is a rare entity. However, in developing countries we still encounter a large number of such cases and the question arises whether CEDH is still a rare entity.
Keywords: epidural hematoma; uncal herniation; neurodeficits; head injury; craniotomy